2020
DOI: 10.3390/cancers12010211
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate Receptor 2 Induces Otoprotective Responses to Cisplatin Treatment

Abstract: Ototoxicity is a major adverse effect of platinum-based chemotherapeutics and currently, there remains a lack of United States Food and Drug Administration-approved therapies to prevent or treat this problem. In our study, we examined the role of the sphingosine 1-phosphate receptor 2 (S1P2) in attenuating cisplatin-induced ototoxicity in several different animal models and cell lines. We found that ototoxicity in S1P2 knockout mice is dependent on reactive oxygen species (ROS) production and that S1P2 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…However, despite its great potential in the treatment of cancer, the use of CP in cancer therapy has a number of disadvantages [55]. One of these is adverse effects on the body's organs and systems resulting from increased production of ROS and stimulation of mitochondrial dysfunction [56][57][58][59].…”
Section: Cisplatin In Cancer Therapymentioning
confidence: 99%
“…However, despite its great potential in the treatment of cancer, the use of CP in cancer therapy has a number of disadvantages [55]. One of these is adverse effects on the body's organs and systems resulting from increased production of ROS and stimulation of mitochondrial dysfunction [56][57][58][59].…”
Section: Cisplatin In Cancer Therapymentioning
confidence: 99%
“…Cisplatin (CP) is a platinumcontaining drug that was first discovered in 1965 and became famous due to its great antimicrobial activity. More experiments demonstrated that platinum-containing agents can possess anti-cancer activity [8][9][10][11][12][13]. As an electrophilic reagent, platinum can interact with nucleophilic residues of nucleobases, including guanine and adenosine by forming covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In order to promote antitumor activity of chemotherapeutic agents, high doses of these agents are applied that substantially enhances side effects on other organs of body. Ototoxicity [ 9 ], hepatotoxicity [ 10 ], nephrotoxicity [ 11 ] and cardiotoxicity [ 12 ] are a few of adverse effects of chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%